2001
DOI: 10.1093/tropej/47.6.350
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potential Risk Factors for Child Malnutrition in Rural Kerala, India

Abstract: Studies indicate that 42-57 per cent of all child deaths in developing countries are due to the potentiating effects of malnutrition on infectious disease, of which over three-quarters can be attributed to mild-to-moderate malnutrition. Risk factors for underweight status in children under 3 years of age were assessed in Kerala, India. Mothers of 34 children weighing below -1 SD for their age and 59 children weighing more than 1 SD for their age, were interviewed for information about maternal health, child fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Several investigators [20,19] have reported an increased risk of infant undernutrition resulting from sub-optimal feeding during early infancy (discarding of colostrum, delayed initiation of breast feeding, pre-lacteal feeding and non-exclusive breastfeeding). However, as in our study, other investigators did not replicate these findings [37,31]. In Bangladesh, food secure households were more likely to practice sub-optimal infant feeding at the age of 3-6 months [38] but the prevalence of undernutrition was significantly lower in this group compared to food insecure households [39].…”
Section: Discussioncontrasting
confidence: 74%
“…Several investigators [20,19] have reported an increased risk of infant undernutrition resulting from sub-optimal feeding during early infancy (discarding of colostrum, delayed initiation of breast feeding, pre-lacteal feeding and non-exclusive breastfeeding). However, as in our study, other investigators did not replicate these findings [37,31]. In Bangladesh, food secure households were more likely to practice sub-optimal infant feeding at the age of 3-6 months [38] but the prevalence of undernutrition was significantly lower in this group compared to food insecure households [39].…”
Section: Discussioncontrasting
confidence: 74%
“…In contrast with expectations, the effect of birth weight was eliminated when the data were placed in a regression equation, even though an association has been reported between low birth weight and subsequent childhood malnutrition in other reviewed studies 5,12,1416. It seems that maternal height as a predisposing factor affecting childhood birth weight is the strongest risk factor, and therefore the effect of birth weight was modified or neutralized in the regression equation.…”
Section: Discussionmentioning
confidence: 91%
“…Phengxay et al in Laos and Veghari and Gholam in Gorgan, Iran, reported male gender as a risk factor for malnutrition in children under 5 years,9,10 but in research by Setswe in Southern Africa,11 Sanghvi et al in Southern India,12 and Saadaat et al in Kashan, Iran,13 female gender was found to be more strongly related to childhood malnutrition. Considering the differences between these studies, it appears that gender is not a biological factor in malnutrition, but affects different stages of childhood growth via various cultural and social factors in different societies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Maternal nutritional status associated with infant and child health has been established previously, but rarely in the aftermath of a crisis (Lima, Figueira and Ebrahim, 1990;Rahman et al, 1993;Mock et al, 1994;Sanghvi et al, 2001;Faber, Swanevelder and Benade, 2005;Rahman and Chowdhury, 2007). Rationing of food consumption is one of the first household responses to a crisis such as a flood (Corbett, 1988).…”
Section: Introductionmentioning
confidence: 99%